2004
DOI: 10.1105/tpc.021162
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Myb Transcription Factor LCR1 Regulates the CO2-Responsive Gene Cah1, Encoding a Periplasmic Carbonic Anhydrase in Chlamydomonas reinhardtii  [W]

Abstract: Chlamydomonas reinhardtii acclimates to CO 2 -limiting stress by inducing a set of genes for a carbon-concentrating mechanism (CCM). This set includes the gene Cah1, which encodes a periplasmic carbonic anhydrase. Although physiological aspects of CO 2 response have been extensively studied, regulatory components, such as transcription factors involved in the acclimation, have not been well described in eukaryotic microalgae. Using an arylsulfatase gene driven by the Cah1 promoter, a regulatory mutant of Cah1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
103
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 37 publications
7
103
0
1
Order By: Relevance
“…After transformation of the chimeric plasmid into the lcr1 mutant, Zeocin-resistant colonies were selected and used for RNA gel blot analyses with a probe specific to the LCI1 coding region ( Figure 3B). The level of endogenous LCI1 mRNAs of 1.3 kb (Burow et al, 1996;Yoshioka et al, 2004) increased in LC-grown Q304P3. In the lcr1 mutant, there was no significant accumulation of the LCI1 mRNA either under LC conditions or in the presence of NO 3 2 , although this mutant previously was shown to accumulate a trace amount of LCI1 mRNA under LC conditions .…”
Section: Induction Of Lci1 By Changing Nitrogen Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…After transformation of the chimeric plasmid into the lcr1 mutant, Zeocin-resistant colonies were selected and used for RNA gel blot analyses with a probe specific to the LCI1 coding region ( Figure 3B). The level of endogenous LCI1 mRNAs of 1.3 kb (Burow et al, 1996;Yoshioka et al, 2004) increased in LC-grown Q304P3. In the lcr1 mutant, there was no significant accumulation of the LCI1 mRNA either under LC conditions or in the presence of NO 3 2 , although this mutant previously was shown to accumulate a trace amount of LCI1 mRNA under LC conditions .…”
Section: Induction Of Lci1 By Changing Nitrogen Sourcementioning
confidence: 99%
“…In addition, the lcr1 mutant showed a 30% decrease in growth rate and a higher apparent K 1/2 (Ci) value compared with that of photosynthetically wild-type strain Q304P3 under LC conditions. Because it has been shown that a loss of CAH1 does not result in reduced growth under LC conditions (Van and Spalding, 1999) and that LCI6 encodes a soluble protein , the putative membrane protein LCI1 was assumed to play a significant role in the CCM (Burow et al, 1996;Yoshioka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In land plants and green algae, the important role of transcription factors during stress responses and development has been demonstrated. For example, CBF1, 2 and 3 direct cold-inducible gene expression in Arabidopsis thaliana (Chinnusamy et al 2007), while Myb transcription factor LCR1 regulates the CO 2 responsive gene Cah1 under CO 2 limiting stress in Chlamydomonas reinhardtii (Yoshioka et al 2004). Moreover, in Volvox carteri, RegA plays a central role as a master regulatory gene in germ-soma differentiation by suppression of reproductive activities in somatic cells (Babinger et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Cah1 promoter is regulated positively and negatively by enhancer and silencer regions. The enhancer region is controlled by two critical elements denoted enhancer-element consensus (Kucho et al, 2003), to which a class of basic-ZIP transcription factors, enhancer-element-consensus binding proteins, interact (Yoshioka et al, 2004). A zinc finger protein, CCM1/Cia5, has been found to be involved in the up-regulation of most low-CO 2 -inducible genes, strongly suggesting that CCM1/Cia5 is a master regulator for the transcriptional response of the Chlamydomonas CCM, but the mechanism of the initial CO 2 signal perception is still unknown (Fukuzawa et al, 2001;Xiang et al, 2001).…”
mentioning
confidence: 99%